2018
DOI: 10.1007/s10517-018-4178-7
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Changes in Metabolic and Hematological Parameters after Transplantation of Pancreatic Islet Cells on TiNi Scaffold in Experimental Diabetes Mellitus

Abstract: The dynamics of the development of the pancreatic islet cells in the porous TiNi scaffold was studied by electron microscopy. Changes in the metabolism of glucose and glycosylated hemoglobin and parameters of the peripheral blood and bone marrow were shown after transplantation of pancreatic islet cells on porous permeable TiNi scaffold during alloxan-induced diabetes. The cells administered on the porous biocompatible scaffold produced more prolonged anti-diabetic effect and normalized hemopoiesis parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Scaffold size, mechanical stability, and diffusion distances affect the choice further. Among the in vivo studies included (n = 91) the ISC/scaffold construct was transplanted into subcutaneous locations (n = 31), 27,51,69,9294,112,115,120,133,135,145,147,156,157,171,212225 the peritoneal cavity (n = 19), 18,26,56,63,6568,101,134,135,173,195,226232 an omental pouch (n = 14), 57,59,81,118,119,163,174,225,233238 the renal capsule (n = 18), 54,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Scaffold size, mechanical stability, and diffusion distances affect the choice further. Among the in vivo studies included (n = 91) the ISC/scaffold construct was transplanted into subcutaneous locations (n = 31), 27,51,69,9294,112,115,120,133,135,145,147,156,157,171,212225 the peritoneal cavity (n = 19), 18,26,56,63,6568,101,134,135,173,195,226232 an omental pouch (n = 14), 57,59,81,118,119,163,174,225,233238 the renal capsule (n = 18), 54,…”
Section: Resultsmentioning
confidence: 99%
“…Scaffold size, mechanical stability, and diffusion distances affect the choice further. Among the in vivo studies included (n = 91) the ISC/scaffold construct was transplanted into subcutaneous locations (n = 31), 27,51,69,[92][93][94]112,115,120,133,135,145,147,156,157,171,[212][213][214][215][216][217][218][219][220][221][222][223][224][225] the peritoneal cavity (n = 19), 18,26,56,63,[65][66][67][68]101,134,135,173,195,[226][227][228][229][230][231]…”
Section: Transplantation Sitementioning
confidence: 99%
“…In vivo tests showed that islet cells with the scaffold could significantly reduce the blood glucose level and decrease the concentration of glycosylated hemoglobin compared to intraperitoneal administration of pancreatic islet cells, indicating that the TiNi scaffold could provide a better microenvironment for islet cells to promote insulin secretion, which consequently achieved better blood glucose control. 132 Roshanbinfar et al encapsulated islet b cells in alginate microcapsules. Compared with the islet b cells without alginate encapsulation, the cells in alginate microcapsules demonstrated significantly higher viability, revealing that alginate encapsulation had good biocompatibility and nutrient availability.…”
Section: Achieving Insulin Secretion By Transplantation Of Pancreatic...mentioning
confidence: 99%